Peningkatan Kreativitas Siswa pada Pembelajaran Ilmu Pengetahuan Alam Sosial Melalui Sumber Belajar di Lingkungan Madrasah Ibtidaiyah Jauharul Ihsan Punti Kalo Muaro Tebo - Alfathul Khairi; Mahluddin Mahluddin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to enhance the creativity of fourth-grade students in learning Natural Sciences (IPA) through the application of science process skills based on the environment at Madrasah Ibtidaiyah Jauharul Ihsan, Punti Kalo. Creativity is an essential aspect of science learning as it helps students develop critical thinking skills, solve problems, and understand scientific concepts more deeply. The research method used is Classroom Action Research (CAR) with a qualitative and quantitative approach. This study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results show that the application of science process skills based on the environment can significantly enhance students' creativity. This improvement is evident in students' active participation in conducting experiments, asking critical questions, and finding solutions to given problems. Additionally, the surrounding environment serves as an effective learning resource in helping students relate scientific concepts to real-life situations. The conclusion of this study is that the science process skills approach based on the environment can be an effective alternative to enhance students' creativity in science learning at Madrasah Ibtidaiyah.